Hindu mythology - MacKay, Jenny frey50 (New York Gale Cengage Learning, 2015)
"This new series from Lucent Books helps younger researchers understand the role of mythology in major historical cultures of the world. Each volume explores the origins and cultural importance of a specific mythology. Presented in an engaging narrative that explains mythology as a product of the culture that created it, each volume details the major characters, gods/goddesses, and themes reflected in the stories. Volumes also discuss the impact of the mythology on daily life at the time and throughout history. Ideal for middle- and high-schools, as well as public libraries, each Mythology and Culture Worldwide volume also features: A list and brief description of the major figures of the mythology, including a family tree illustrating their relationships; Five to six chapters exploring the mythology in detail; Informative sidebars highlighting related topics; Fact boxes providing at-a-glance information; Full-color maps, photographs and illustrations; A glossary of terminology; "For More Information" list of sources of additional information; A comprehensive index"--
"This new title in the Mythology and Culture Worldwide series discusses the origins of Hindu myths and how some of these myths have been manipulated over time. The book details the major gods found within the mythology along with some of the most memorable tales, such as creation of the world and the making of humanity. The title ends with how Hindu myths have penetrated popular culture"--
Includes bibliographical references and index
Keywords: Hindu mythology -- Juvenile literature; Social Science -- General; Social Science -- Folklore & Mythology; JUVENILE NONFICTION / People & Places / Asia; Juvenile works